INCREASING STUDENTS’ VOCABULARY MASTERY BY GUESSING GAME - Sri Sudaryati; Nasriani Nasriani; Fajar Alamsyah (Universitas Madako Tolitoli, 2020)
This research was about increasing students’ vocabulary mastery by using guessing game at the third grade of Madrasah Al-Munawwarah Tambun. The design of this research was pre experimental research. The sample of this research were the third grade that consists of 16 students. The data obtained from pre test and post test. In the pre test it was found that mean score of the student were 65,37 and in the post test were 79,87. Computation of the data tcount results was5,069while ttablewas 2,131. The result indicates that there is an increasement in students’ vocabulary mastery by using guessing game. It can be concluded that increasing vocabulary mastery by using guessing game is effective to increase students’ vocabulary mastery.Keywords: : Increasing, vocabulary mastery, Guessing game